Analysis of 1, 3 dimethylamylamine concentrations in Geraniaceae, geranium oil and dietary supplements. Issue 7 (22nd May 2013) - Austin, Krista G.; Travis, John; Pace, Gerry; Lieberman, Harris R.; Brandt, Simon D.
<x xml:space="preserve">Abstract</x> 1, 3‐Dimethylamylamine (DMAA) is a sympathomimetic compound currently incorporated into some dietary supplements. Significant controversy exists regarding the 'natural' origin of DMAA, as claimed by manufacturers of supplements. Manufacturers often refer to its presence by the name Geranamine® implying that DMAA is found in the plant species Geranium and Pelargonium known collectively as Geraniaceae. This study determined whether DMAA is present in the plant species, Geranium and Pelargonium. In addition, concentrations of DMAA in popular dietary supplements and commercial Geranium and Pelargonium oils were assessed. One Pelargonium cultivar, one Geranium cultivar, three essential oils from Pelargonium or Geranium, raw DMAA powder, and seven dietary supplements (DS) sold as finished products and labelled as containing DMAA, or one of its synonyms, were analyzed for the presence of DMAA by ultra performance liquid chromatography tandem mass spectrometry (UPLC‐MS/MS). No measurable levels of DMAA in Geranium, Pelargonium or essential oils at a detection limit of 1–2 ng/g were present. UPLC/MS/MS analysis confirmed the presence of DMAA in spiked plant and oil samples, all seven DS products, and raw DMAA powder. Concentrations (weight%) of DMAA provided in DS ranged from 0.11% to 673%. This study indicates DMAA contained in DS is of a synthetic origin and is not present in the plant species Geranium and Pelargonium; thus the 'natural' origin and use of DMAA as an ingredient in DS is not substantiated. Copyright © 2013 John Wiley & Sons, Ltd.